The Theory of Syarî‘ah Oriented Public Policy - Saim Kayadibi (Universitas Islam Negeri Jakarta, 2015)
Siyasah syar’iyyah theory oriented in public policies that reflect sharia Islamic government policy.Islam, which covers all aspects of human life, from worship to mu'amalat, from siyasah (good governance) to 'alaqât al-dawliyyah (international relations), has a particular system of government and policy. Therefore, this article analyses the theory, starting from the definition, background, types, and its purpose.DOI: 10.15408/ajis.v15i2.2861